THE ROLE OF BUSINESS STRATEGIES ON RELATION INTELLECTUAL CAPITAL ELEMENT AND CORPORATE PERFORMANCE - Masri, Indah (Jurnal ASET (Akuntansi Riset), 2016)
Abstract. The aim of the research is examine the effect of intellectual capital elements on the financial performance of companies with business strategy as moderation. Using data publicly traded company listed on the Indonesia Stock Exchange in the period 2010 to 2013. Testing is done to see the direct influence of the elements of intellectual capital with the company's financial performance. The results showed that of the three elements of intellectual capital that is used in this study (human capital, process capital, customer capital), finds that process capital positive and significant effect on the rate of 5% can improve financial performance of companies. The results support the research conducted by Wang and Chang (2005). Moderation intellectual capital elements with its business strategy shows that process capital is more appropriate in the innovation strategy rather than cost efficiency strategy, because in process capital attached to the innovation and creativity. On the human capital, moderation with an innovation strategy and cost efficiency strategy showed a significant result negative. Explains that the innovation strategy and cost efficiency strategy is not appropriate in human capital, because it weakens positive relationship human capital with the company's financial performance. For moderation customer capital with its business strategy both innovation and cost-efficiency strategy showed no significant results. It is clear that the selection of the company's strategy does not affect the customer capital. The results of this study also confirms some earlier studies on the effect of customer capital on the company's performance is inconsistent. Keywords: cost efficiency strategy;customer capital; financial performance; human capital; innovation strategy; process capital.Â Abstrak. Tujuan penelitian ini adalah menguji pengaruh unsur modal intelektual terhadap kinerja keuangan perusahaan dengan strategi bisnis sebagai moderasi. Menggunakan data perusahaan publik yang terdaftar di Bursa Efek Indonesia pada periode 2010 hingga 2013. Pengujian dilakukan untuk melihat pengaruh langsung dari unsur modal intelektual dengan kinerja keuangan perusahaan. Hasil penelitian menunjukkan bahwa dari ketiga unsur modal intelektual yang digunakan dalam penelitian ini (sumber daya manusia, modal proses, modal pelanggan), menemukan bahwa proses modal positif dan signifikan berpengaruh pada tingkat 5% dapat meningkatkan kinerja keuangan perusahaan. Hasil mendukung penelitian yang dilakukan oleh Wang dan Chang (2005). Unsur modal intelektual moderasi dengan strategi bisnisnya menunjukkan bahwa modal proses lebih tepat dalam strategi inovasi daripada strategi efisiensi biaya, karena dalam proses kapital melekat pada inovasi dan kreativitas. Pada human capital, moderasi dengan strategi inovasi dan strategi efisiensi biaya menunjukkan hasil negatif yang signifikan. Menjelaskan bahwa strategi inovasi dan strategi efisiensi biaya tidak tepat dalam human capital, karena itu memperlemah hubungan positif human capital dengan kinerja keuangan perusahaan. Untuk modal pelanggan moderasi dengan strategi bisnisnya baik inovasi dan strategi efisiensi biaya menunjukkan tidak ada hasil yang signifikan. Jelas bahwa pemilihan strategi perusahaan tidak mempengaruhi modal pelanggan. Hasil penelitian ini juga menegaskan beberapa studi sebelumnya tentang pengaruh modal pelanggan terhadap kinerja perusahaan yang tidak konsisten.Kata Kunci: cost efficiency strategy;customer capital; financial performance; human capital; innovation strategy; process capital.